Peningkatan Profesionalisme Guru Melalui Inovasi Pembelajaran - Muhammad Kristiawan; Nur Rahmat (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
To create a better quality of education, it was necessary to take various actions that support learning in the classroom. This laziness causes low quality education. The low quality of education at this time was an indication of the need for professional teachers. The purpose of this study provided an overview of improving teachers’ professionalism through learning innovation. The research used a qualitative descriptive study. Data were collected by observation, interviews, and documentation. Objects in this study were teachers of SD Negeri 3 Rejosari, SD Negeri 1 Purwodadi, SD Negeri 2 Srimulyo in Belitang Mulya, SD Negeri 1 Karang Endah, and SD Negeri 1 Taraman, Semendawai Suku III Ogan Komering Ulu Timur, South Sumatra. The results indicated that the teachers must be equipped by knowledge and motivation, then the teachers can improve their service to students through their teaching skills. Learning objectives in educational institutions generally need innovation, so they can develop their skill based on the dynamics of life. The effort can be done in order to improve teachers’ professionalism was by learning innovations. The learning innovations were be able to improve the previous learning to a better direction, giving an overview to other parties about the implementation of innovation, and others can also try out the innovations made, encourage them to continue on developing knowledge. The increasing quality of teachers’ professionalism will improve the quality of education both process and outcome. Key words: Teachers’ Profesionalism, Learning Innovation, Primary School